PERAN ORANGTUA DALAM MENGATASI PERILAKU AGRESIFITAS ANAK USIA REMAJA DI DESA TALIO KECAMATAN HILISALA’AHE TAHUN 2021 - Yapieli Ndruru (Universitas Nias Raya, 2022)
The problem in this research is that children who are teenagers tend to show an aggressive attitude at home and in society. The aims of the study were 1) to identify and describe the factors that influence aggressive behavior in adolescent children and 2) to identify and describe the role of parents in overcoming aggressive behavior in adolescents. The type of research is a qualitative approach. Technique of data collection is interview. The results showed that the factors that influence the aggressive behavior of adolescent children are internal factors in the form of birth defects, weak self-control, lack of adjustment and lack of religious basis, while external factors come from the family, community and school environment. The role of parents in overcoming the aggressive behavior of adolescent children is to take an empathetic approach, manage anger, give punishment, give love, play with children, do fair treatment, use art in guiding children, channeling children's anger, nurturing, educating, protecting and giving. education, setting an example of a good personality and directing children to excel. So it can be concluded that the role of parents in overcoming aggressive behavior in children is in the form of an empathetic approach, giving punishment and affection. Suggestions can be put forward by researchers are 1) parents should overcome the aggressive behavior of adolescent children by taking an empathetic approach, giving love and giving educational punishments, 2) adolescent children should be able to control and control themselves not to do aggressive behavior that can harm themselves and others by controlling emotions, and 3) further researchers should be able to conduct relevant research and at a broader level.